Leadership and gender perspective in hospital physiotherapy units - Margelí, Mercedes Ferrando; Sánchez, Aitor Garay; Andrade-Gómez, Elena; Suarez-Serrano, Carmen; Marcén-Román, Yolanda (Scientific reports, 2024)
Analyze the gender stereotypes present in the leaders of the Hospital Physiotherapy Units, determine the level of acceptance of female leadership and identify which factors influence these perceptions. Observational, descriptive, exploratory and cross-sectional study. The study subjects are the census of leaders of the Physiotherapy Units of public hospitals. The measurement instruments used are the Acceptance of Female Leadership Questionnaire (ACT-LM), and the sociodemographic and job-related variables. Most of the leaders of the hospital physiotherapy units were women (69.4%) physiotherapists. Gender stereotypes emerge in the dimension of Instrumental Characteristics, with respondents not fully agreeing that women were sufficiently competitive (18.7%) or ambitious (20.8%) to be successful in the world of work. These data were influenced by gender, showing that men have a higher regard for female leadership abilities than women themselves. In the dimension of Acceptance of Female Leadership, 17.4% of those surveyed did not fully agree that women can rise to the same extent as men. Most of the leaders of the physiotherapy units in public hospitals in Spain are women, this is reversed in favor of men in highly complex hospitals. The stereotype persists, especially among women, that they do not have enough ambition and competitiveness to succeed in the world of work.